Embryo utilisation rate and transferable embryo to oocyte ratio correlate positively with livebirth rate but negatively with oocyte number: analysis of 14,156 fresh IVF/ICSI cycles - Adrija Kumar Datta; Geeta Nargund; Martin Wilding; Sam Dobson; Stuart Campbell (Journal of Ovarian Research)
Abstract Background The live birth rates (LBRs) do not rise after a certain number of oocytes are collected in fresh IVF cycles. Although the detrimental effect of high ovarian response on the endometrium has been recognised, the effect of high oocyte yield on oocyte competency remains disputed. The purpose of this study was to examine whether high oocyte yield adversely affect the competency of oocytes or embryos. We retrospectively analysed UK’s National database (published by Human Fertilisation and Embryology Authority (HFEA)- year 2015–2016) including couples who underwent first IVF treatment with single embryo transfer or had no available embryo, due to tubal or unexplained infertility among women aged < 40 years. Results Retrospective analysis of 14,156 fresh IVF/ ICSI cycles that met the inclusion criteria revealed an inverse correlation between Embryo Utilisation Rate (EUR) and the oocyte yield (r= -0.250047, p < 0.0001). The Transferable Embryo to Oocyte Ratio (TEOR) also inversely correlated with the number of retrieved oocyte (r = − 0.331431, p < 0.0001). The number of oocytes that did not produce transferable embryos had a stronger positive correlation with oocyte yield (r = 0.916676, p < 0.0001) than those produced transferable embryos (r = 0.569972, p < 0.0001). Both EUR (p = 0.01) and TEOR (P < 0.0001) correlated positively with the live birth except in the women age-group of 38–39 years. Although fertilisation rates remained similar, both EUR and TEOR declined steadily with the increasing number of oocytes until it reached a nadir at around 8–9 oocytes. At this point the LBR in fresh cycles reached its peak. Conclusion The EUR and TEOR decline with increasing oocyte yield while both the ratios have a positive correlation with live birth. Despite declining EUR and TEOR, increasing oocyte yield can still boost fresh cycle LBR until the proportions of transferable embryos fall to a nadir. Thus, the focus needs to be on finding more efficient method for embryo selection and avoid generating too many wasteful oocytes that only pose more risk or raise cost without improving fresh cycle LBR. Trial number Being a retrospective study, prior registration of the trial was not required. Clinical trial number Not applicable.